Excess body iron and the risk of type 2 diabetes mellitus: a nested case–control in the PREDIMED (PREvention with MEDiterranean Diet) study. Issue 11 (17th October 2014) - Arija, Victoria; Fernández-Cao, José C.; Basora, Josep; Bulló, Mònica; Aranda, Nuria; Estruch, Ramón; Martínez-González, Miguel A.; Salas-Salvadó, Jordi
Abstract : A prospective nested case–control study within the PREvention with MEDiterranean Diet (PREDIMED) was conducted to evaluate the relationship between excess body Fe (measured as serum ferritin (SF), soluble transferrin receptor (sTfR) and sTfR:ferritin ratio) and the risk of type 2 diabetes mellitus (T2DM) in a Mediterranean population at a high risk of CVD, without T2DM at the start of the study. The study contained 459 subjects, 153 with incident T2DM (cases) and 306 without incident T2DM (controls). The follow-up period was for 6·0 (interquartile range 3·9–6·5) years. For each incident diabetic subject, two subjects were selected as controls who were matched broadly for age as well as for sex, intervention group and BMI. We observed a relationship between SF values >257 μg/l in males and >139 μg/l in females and the risk of T2DM, following adjustment in the conditional logistic regression model for high-sensitivity C-reactive protein, fasting glucose and other components of the metabolic syndrome (OR 3·62, 95 % CI 1·32, 19·95; P = 0·022). We also found an association between low sTfR:ferritin ratio levels and the incidence of T2DM (OR 3·02, 95 % CI 1·09, 8·39; P = 0·042), but no association with sTfR (OR 1·29, 95 % CI 0·51, 3·23; P = 0·722). Oxidative stress has been hypothesised to contribute to the development of insulin resistance and β-cell dysfunction, the two key events in the clinical development of T2DM. Following adjustment for other risk factors for T2DM, excess body Fe (measured as SF and sTfR:ferritin ratio) was associated with an increased risk of developing T2DM in a Mediterranean population at a high risk of CVD.